2020
DOI: 10.3389/fbioe.2020.00223
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulants Interfere With the Angiogenic and Regenerative Responses Mediated by Platelets

Abstract: Background and aims: Platelet rich plasma (PRP) obtained from blood anticoagulated with acid-citrate-dextrose (ACD) or sodium-citrate (SC) is used for regenerative medicine as source of platelet-derived growth factors. Allergic reactions against citrate were reported in patients after local injection of PRP allowing us to hypothesize that anticoagulants exert a harmful and local effect that interferes with the regenerative proprieties of platelets. Herein we test this hypothesis by analyzing the effect of ACD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…One strategy that was proposed several years ago for the regeneration of intrabony defects was the use of platelet concentrates [10]. While platelet-rich plasma (PRP) was proposed as a first-generation platelet concentrate, the use of anticoagulants has since been shown to interfere with the angiogenic and regenerative responses mediated by platelets [11]. For these reasons, a second-generation platelet concentrate, termed platelet-rich fibrin (PRF), has more been introduced in regenerative medicine and dentistry [10,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…One strategy that was proposed several years ago for the regeneration of intrabony defects was the use of platelet concentrates [10]. While platelet-rich plasma (PRP) was proposed as a first-generation platelet concentrate, the use of anticoagulants has since been shown to interfere with the angiogenic and regenerative responses mediated by platelets [11]. For these reasons, a second-generation platelet concentrate, termed platelet-rich fibrin (PRF), has more been introduced in regenerative medicine and dentistry [10,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…With that purpose, we isolated exosomes exclusively released by PRP platelets, which were free of contaminants from other components present in PRP, allowing us to analyze pure PLT-Exos and to evaluate the influence of platelet activation by CaCl 2 on their molecular composition. It must be taken into consideration that the activation method chosen may modify the molecular release [ 30 ]. The activation method employed here based on CaCl 2 addition, is one of the most commonly used procedures to induce the release of molecular mediators from PRP platelets and avoids the use of exogenous biomolecules such as thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, CaCl 2 -activation prevents local hypocalcemia caused by calcium chelating anticoagulants required for blood collection in the PRP preparation. A recent study showed that calcium restitution is necessary to prevent cellular and tissue alterations due to the anticoagulants used in some PRP preparations [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, growth factors can induce both anabolic and catabolic effects on cells [43] thus potentially affecting the cellular response. Another important aspect to take into account is the contribution of citrate deriving from anticoagulant ACD-A presents in the PRP units, primarily for its role as calcium chelator, which has been demonstrated to interfere with the angiogenic and regenerative proprieties of platelets [44]. On the other hand, some authors studying the specific effect of different concentrations of citrate supplementation in promoting bone regeneration, observed that exogenous supplementation of citrate is dose-dependent and that 200 ”M is the optimal concentration able to induce the elevation of osteogenic markers [45].…”
Section: Discussionmentioning
confidence: 99%